Intra-Party Crisis and Decline of Opposition Parties in Nigeria: An Assessment of the People’s Democratic Party, 2015-2025 - Onyekwere, Chibuike Sylvester Onyekwere; Ololo, Ejike Emmanuel Ololo (African Journal of Stability and Development (AJSD), 2025)
The study interrogated intra-party crisis and the decline of opposition parties in Nigeria, focusing on the People’s Democratic Party (PDP). It tried to examine the challenges and effects of the intra-party crises in the PDP, most especially in the area of providing a credible and viral alternative that can consolidate Nigeria’s democracy. The study was anchored on elite theory, and the qualitative method of data collection was used to glean data from observation and documentary evidence of secondary sources. The ex-post-facto research design and qualitative descriptive analysis were employed with logical induction in analysis. The study revealed that the perennial crises within the PDP, precipitated by the normless character of politics and partisan relations, have depleted the strength of the party and equally undermined its fortunes as the major opposition party in Nigeria. Based on our findings, the paper makes a case for ideologically based partisanship as a panacea to the problem.